Electrochemical peroxidation of contaminated water and assessment of the toxicity using existing and novel bioassays - Kokkali, Varvara (Cranfield University, 2011)
The treatment of wastewater and monitoring of its toxicity is essential before discharging it to the environment. This study focuses on assessing the toxicity of wastewater following treatment using the electrochemical peroxidation process (ECP). Three categories of low-cost toxicity assays were used based on plant cells, microorganisms and invertebrates, all of which do not require ethical approval or a special licence. In addition, a novel cost-effective device was developed for assessing wastewater toxicity at low concentrations. In Chapter 2, the problem of high turbidity of the ECP-treated samples is addressed, by accelerating particulate settling of the existent compounds. This was achieved by storing the ECP treated samples at low temperatures. This is an essential step for enhancing the clarity of the processed samples in order to improve the performance of the toxicity assays. Cont/d.